2015
DOI: 10.4037/ajcc2015435
|View full text |Cite
|
Sign up to set email alerts
|

Lived Experience of the Intensive Care Unit for Patients Who Experienced Delirium

Abstract: Background Delirium is a common occurrence for patients in the intensive care unit and can have a profound and lasting impact on them. Few studies describe the experience of intensive care patients who have had delirium. Objective To understand the lived experience of intensive care for critically ill patients who experienced delirium. Methods The study parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…Tse et al [21] proposed that age as well as certain pre-existing diseases and conditions are predictors of delirium after cardiac surgery. There are no recommended drugs or drug regimens to prevent delirium, so the focus should be on non-pharmaceutical interventions, including active communication, early detection of patients' psychological problems, family companionship, early activities, noise reduction, and good sleep [22].…”
Section: Discussionmentioning
confidence: 99%
“…Tse et al [21] proposed that age as well as certain pre-existing diseases and conditions are predictors of delirium after cardiac surgery. There are no recommended drugs or drug regimens to prevent delirium, so the focus should be on non-pharmaceutical interventions, including active communication, early detection of patients' psychological problems, family companionship, early activities, noise reduction, and good sleep [22].…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, delirium is a distressing experience for patients, families, carers and healthcare staff (Grover 2014;Martins 2016). Qualitative research has reported on the experiential distress and resulting features of anxiety and depression that patients have after an in-patient episode of delirium (Whitehorne 2015). In particular, post-traumatic stress disorder (PTSD) is emerging as a recognised consequence of delirium and it has been suggested that it should be more routinely followed up, given its potential impact on patient recovery and quality of life (Teale 2013;Bolton 2019).…”
Section: Recoverymentioning
confidence: 99%
“…Recovery from delirium is an ill-defined concept in the literature, and although it is widely considered that delirium is often reversible, accumulating evidence suggests that it is often marked by incomplete resolution (Witlox 2010; Adamis 2014). Indeed, it has been found that, for each day a patient has delirium in the emergency department, a significantly worse long-term cognitive and functional outcome has been reported (Han 2017).…”
Section: Recoverymentioning
confidence: 99%
“…Some patients reported they heard music, sea waves, or had visions of dark or colorful tunnels; others felt like sailing on a ship. They also reported they felt they could be in several places such as a race track, a beauty salon, a building, a nightclub, describing in detail the characteristics of each place (15) .…”
Section: Real and Illusory Perceptions Of Patients In Induced Comamentioning
confidence: 99%